Evaluasi Penerapan Fit to Work Guna Peningkatan Kesehatan dan Keselamatan Kerja di Terminal Kalimas Surabaya - Novirina Hendrasarie; lham Lacta Praditya (Fakultas Teknik, 2023)
Every year around 24 million people die from work accidents, which include 360,000 fatal accidents and it is predicted that 1.95 million of them are caused by fatal diseases that arise in the work environment. PT Pelindo III is a company that serves as a public port operator (terminal operator). In 2011 according to the Ministerial decree of Transportation Number: KP 88 of 2011 concerning the granting of a business license to PT Pelabuhan Indonesia III (Persero) as a Port Business Entity covering the provision and service. Therefore, the function of PT Pelabuhan Indonesia III also increases. Evaluation is one of the stages in the process of carrying out a fit to work health examination which aims to provide recommendations for developing the process. The purpose of this examination is to study the implementation of the program on fit to work which discusses efforts in implementing occupational health and safety at the Kalimas Terminal in Surabaya. In this study using quantitative descriptive research as a research design with interview and survey methods. The informants of this study were 11 people from Kalimas Terminal employees. The results obtained in this study are the implementation of fit to work program at Kalimas Surabaya Terminal has been carried out optimally and effectively